Photographs of an intersex body: between the punctum and the trochus - Murugarren, Macarena (Área Feminismos, Género y Sexualidades del Centro de Investigaciones "María Saleme de Burnichón" de la Facultad de Filosofía y Humanidades, Universidad Nacional de Córdoba, 2021)
In this article I will present a reflection on the methodological issues that arise in my graduate thesis, in which I analyze the representation of an intersex body and its relation to the category of eroticity in the photographic series inter*ME by lx artistx inter* Del LaGrace Volcano. The present reflection explores the question of how to constitute a methodology that allows me to link my activism and my theoretical-methodological framework when working with my corpus. For this reason I will present Barthes' punctum and Didi-Huberman's troche categories and explain the reasons why I consider the interweaving of the two to constitute a situated methodology that can express the way my intersex body looks at images of another intersex body from an eroticizing gaze.